Uslub Nahyu Dalam Kajian Metode Tafsir Al-Quran - Yusuf Bahtiar; Aam Abdussalam (ZAD Al-Mufassirin, 2020)
The purpose of this discussion is to find out Uslub Nahyu in the study of the Qur'anic Interpretation method. Uslub Al-Quran is a method of analysis and a refrensive approach in compiling his sentences and the selection of his lafaz-lafaz. Uslub Al-Quran has characteristics, namely: The touch of lafaz al-Quran through the beauty of the intonation of the Qur'an and the beauty of the language of the Qur'an, acceptable to all walks of life, the Qur'an touches (accepted) reason and feelings, the compatibility of the Quran's sequence of sentences and the richness of editorial art. Uslub nahyu is the opposite of amr, which is a lafaz that shows the demand to leave something from the superior to the subordinates or the word nahyu on the number of al-nahy (Prohibition sentence) as a speech conveyed by the higher party of his position to the party below him or the lower party in order to leave something deed.